Seeking to improve access to COVID-19 therapeutics in the remote Torres and Cape communities of Far North Queensland during the first COVID-19 omicron outbreak - Sarah Galloway; Caroline Taunton; Rittia Matysek; Allison Hempenstall (James Cook University, 2022)
Introduction: The first outbreak of the omicron variant of COVID-19 in the Torres and Cape region of Far North Queensland in Australia was declared in late December 2021. A COVID-19 Care at Home program was created to support the health and non-health needs of people with COVID-19 and their families throughout the mandatory isolation periods and included centralising the coordination and delivery of COVID-19 therapeutics. The therapeutics available included one intravenous monoclonal antibody (sotrovimab) and two oral antiviral therapies: nirmatrelvir and ritonavir (Paxlovid®) and molnupiravir (Lagevrio®). This article describes the uptake and delivery of this therapeutics program. Methods: COVID-19 cases were documented in a notification database, screened to determine eligibility for COVID-19 therapies and prioritised based on case age, vaccination status, immunosuppression status and existing comorbidities, in line with Queensland clinical guidelines. Eligible cases were individually contacted by phone to discuss treatment options, and administration of therapies were coordinated in partnership with local primary healthcare centres and hospitals. Results: A total of 4744 cases were notified during the outbreak period, of which 217 (4.6%) were deemed eligible for treatment after medical review. Treatment was offered to 148/217 cases (68.2%), with 90/148 cases (60.8%) declining treatment and 53/148 cases (35.8%) receiving therapeutic treatment for COVID-19. Among these 53 cases, 29 received sotrovimab (54.7%), 20 received Paxlovid (37.7%) and four received Lagevrio (7.5%). First Nations people accounted for 48/53 cases (90.6%) who received treatment, and COVID-19 therapeutics were delivered to cases in 16 remote First Nations communities during the outbreak period. Conclusion: The COVID-19 Care at Home program demonstrated a novel, public health led approach to delivering time-critical medications to individuals across a large, remote and logistically complex region. The application of similar models to outbreaks and chronic conditions of public health importance offers potential to address many health access inequities experienced by remote Australian First Nations communities.